1986
DOI: 10.1073/pnas.83.16.5983
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-mediated folate accumulation is regulated by the cellular folate content.

Abstract: Cultured monkey kidney cells are shown to possess a cell-surface receptor that binds 5-methyltetrahydro [3',5',7,9-3H4] Folates are a class of pteridine compounds that are essential for normal growth and maturation. Reduced folic acid coenzymes are involved in one-carbon transfer reactions such as those necessary for the biosynthesis of methionine, serine, deoxythymidylic acid, and purines. Although these folatemediated reactions have been studied extensively and many of the key enzymes that catalyze these rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
207
1
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(217 citation statements)
references
References 14 publications
8
207
1
1
Order By: Relevance
“…Because these culture conditions ensured adequate delivery of folate to all cell lines used, the differential cisplatin responsiveness cannot be attributed to different availability of endogenous folates but instead might reflect differences in the capacity to use them. FBP expression levels have been reported to be inversely regulated by the extra-and intracellular folate concentration (Kamen et al, 1986;Kane et al, 1988) but, in our hands, only one (L-SKOV3) out of five ovarian carcinoma cell lines tested showed FBP up-modulation when adapted at physiological folate concentrations (20 nM) . In the same study, all the cell lines showed a marked decrease in endogenous folates compared with cells grown in standard medium (2.3 ,UM), and the amount of total folate in the cells was in general directly proportional to the level of membrane FBP expression, consistent with the concept that intracellular folate content is maintained primarily by FBP in low-folate cultured cells (Matsue et al, 1992 (Table).…”
Section: Discussionmentioning
confidence: 50%
“…Because these culture conditions ensured adequate delivery of folate to all cell lines used, the differential cisplatin responsiveness cannot be attributed to different availability of endogenous folates but instead might reflect differences in the capacity to use them. FBP expression levels have been reported to be inversely regulated by the extra-and intracellular folate concentration (Kamen et al, 1986;Kane et al, 1988) but, in our hands, only one (L-SKOV3) out of five ovarian carcinoma cell lines tested showed FBP up-modulation when adapted at physiological folate concentrations (20 nM) . In the same study, all the cell lines showed a marked decrease in endogenous folates compared with cells grown in standard medium (2.3 ,UM), and the amount of total folate in the cells was in general directly proportional to the level of membrane FBP expression, consistent with the concept that intracellular folate content is maintained primarily by FBP in low-folate cultured cells (Matsue et al, 1992 (Table).…”
Section: Discussionmentioning
confidence: 50%
“…Then cells were centrifuged and the cell pellet was analyzed for radioactivity. The total folic acid binding capacity was determined after a 20 min acidic treatment with HBSS buVer (pH 3.5) to remove surface bound folates [29]. After centrifugation, cells were resuspended in HBSS pH 7.4 and incubated with [ 3 H]-folic acid as described above.…”
Section: Ex Vivo Folic Acid Binding Studiesmentioning
confidence: 99%
“…Membrane folate receptors are membrane-associated folate binding proteins that constitute a second group of folate transporters and are characterized by high binding aYnity for folic acid (K d : 0.1-1 nM) and 5-methyltetrahydrofolate (K d : 3 nM), but markedly lower aYnities for other reduced folates and MTX [26,29,44,64].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that in several cases FBP expression is physiologically regulated by the intracellular folate content (Kamen and Capdevila, 1986;Kane et al, 1988;Matsue et al, 1992;Miotti et al, 1995), most probably by the 5-methyltetrahydrofolate (5-CH3-H4 folate) content, since this coenzyme is the natural ligand of FBP and represents the predominant circulatory form (>90% of the overall seric folate, under physiological conditions) (Antony, 1992). Intracellular 5-CH3-H4 folate shortage may be consequent on limited bioavailability of extracellular folates or on biochemical defects in the intracellular regeneration or cellular retention of this folate form.…”
mentioning
confidence: 99%